Mini Review: GLP-1 Modification, Development, and Improvement - Damai, Fedric Intan; Purwanto, Gracia Christine Lembong; Wardiana, Andri; Wisnuwardhani, Popi Hadi; Agustiyanti, Dian Fitria; Fathurahman, Alfi Taufiq; Ningrum, Ratih Asmana (Annales Bogorienses, 2022)
Diabetes Mellitus Type 2 (DM-2) is the condition where the body comes to be insensitive or even resistant towards insulin, thus resulting in deficient insulin secretion from beta cells in the pancreas. Compared with the available treatments, Glucagon-like peptide 1 (GLP-1) is considered a natural treatment to cure DM-2 due to its characteristic as an incretin hormone, where one of its functions is to improve insulin secretion and enhance beta-cell glucose sensitivity. However, GLP-1 has a limitation, which is a rapid half-life due to active degradation activities in the body. Therefore, many studies have been conducted to develop and improve the pharmacological activity of GLP-1 through structural modification and yield improvement, which are thoroughly reviewed in this paper. Structural modification of GLP-1 covers amino acid substitutions by referring to the GLP-1 analog, Exendin4, to prevent the dipeptidyl peptidase-4 (DPP-4) degradation activity and protein fusion with an additional chain to extend the half-life during administration. The yield improvement at the overexpression of GLP-1 tandem repeats sequences can increase the transcribed genes’ yield. The studies show that specific amino acid substitutions and IgG heavy chain constant regions or Fc-based fusion genes successfully enhance the pharmacological activities of GLP-1. At the same time, Pichia pastoris expression system managed to yield 219.2 mg/l target protein, where the purified target protein is capable of producing 10× yield of a single GLP analog. Further research could include the utilization of these findings in vitro as a GLP-1 analog-based therapeutics to treat DM-2.